The role of the boards' financial expertise in the investment dynamics of businesses in emerging markets - Rehana Naheed; Sohail Rizwan; Muhammad Jawad; Munazza Naz (Cogent Business & Management, 2022)
This study examines the impact of the financial expertise of the board of directors (BOD's) on the investment decisions of firms by integrating Sarbanes-Oxley (SOX) regulations. The study has taken into account two emerging markets China and Pakistan from 2009-2020 with 8000 and 1120 firm-year observations respectively. The study has used fixed effect, random effect, and generalized method of moments (GMM) estimation techniques. The findings of the study are twofold. Firstly, BFE is positively related to firm investment and shows that financial experts on the board help firms to access financial resources for the firms. Secondly, the sub-sample results show the impact of BFE on investment is more profound for the firms that are large, financially unconstrained, with a strong balance sheet position, and faceless competition. This study introduces BFE as a contributing factor in the investment decisions of the firm. To the researchers' best knowledge, no previous study has focused on BFE as a contributing factor in firms' investment. The findings of the study are following the resource-based view.
Keywords: 650; Investment; emerging markets; resource-based view; boards' financial expertise